Knowledge and Attitude towards Exclusive Breast Feeding among Mothers Attending Antenatal and Immunization Clinic at Dabat Health Center, Northwest Ethiopia: A Cross-Sectional Institution Based Study - Mulugeta Wassie Alamirew; Netsanet Habte Bayu; Nigusie Birhan Tebeje; Selam Fiseha Kassa (Nursing Research and Practice)
Introduction. To assess knowledge and attitude towards exclusive breast feeding among mothers attending antenatal care and immunization clinic in Dabat Health Center, Northwest Ethiopia, 2016. Methodology. Institutional based descriptive cross-sectional study was conducted. The data was collected by using pretested, structured interview based questionnaires. The data were entered and analyzed using SPSS version 20. Result. A total of 384 participants were included in the study with a response rate of 100%. The majority were in the age groups of 20–30 (66.9%) and the mean age was 27.65; 325 (84.6%) were Orthodox Christianity followers. Majority were of Amhara ethnicity 370 (96.4%). Based on knowledge score, 268 (69.8%) were grouped as having good knowledge and regarding attitudinal score, 92 (24%) of the study participants were categorized as having negative attitude towards exclusive breast feeding (EBF) and the remaining 292 (76%) were categorized as having positive attitude. Conclusion. In this study, the knowledge of study participant mothers towards EBF is low which is less than three-fourths; however positive attitude towards EBF is more than three-fourths in this study. The authors recommend that health care workers who work in the areas of maternal and child health clinic should give appropriate information about EBF.